2013
DOI: 10.1638/2012-0240r2.1
|View full text |Cite
|
Sign up to set email alerts
|

SEROPREVALENCE OFBORRELIA BURGDORFERISENSU LATO IN ROE DEER (CAPREOLUS CAPREOLUS) FROM NORTHWESTERN SPAIN

Abstract: In the present study, the seroprevalence of Borrelia burgdorferi sensu lato in roe deer in relation to different parameters in northwestern Spain was investigated. A total of 154 roe deer hunted between April 2007 and October 2008 from different localities of Galicia (northwest Spain) were examined. From each animal, a blood sample and all attached ticks found were collected. All the specimens for tick stages (larva, nymph, and adult) were speciated based on reference keys. Antibodies against B. burgdorferi we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
(14 reference statements)
2
9
0
Order By: Relevance
“…In total, 8885 ticks were collected; all developmental stages of I. ricinus were found infesting roe deer, with adult females being the most frequent, followed by nymphs, males and larvae (Table 1); these differences were significant by a Kruskal-Wallis test ( 2 = 87 145; P < 0.001). Our results corroborate those of Vázquez et al (2011) and Pato et al (2013), who found that, in addition to adults, deer could also support a high proportion of immature stages. The median number of ticks infesting roe deer was similar in both areas (Table 1) and the differences were not significant using the Kruskal-Wallis test (P > 0.05).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In total, 8885 ticks were collected; all developmental stages of I. ricinus were found infesting roe deer, with adult females being the most frequent, followed by nymphs, males and larvae (Table 1); these differences were significant by a Kruskal-Wallis test ( 2 = 87 145; P < 0.001). Our results corroborate those of Vázquez et al (2011) and Pato et al (2013), who found that, in addition to adults, deer could also support a high proportion of immature stages. The median number of ticks infesting roe deer was similar in both areas (Table 1) and the differences were not significant using the Kruskal-Wallis test (P > 0.05).…”
Section: Resultssupporting
confidence: 91%
“…() and Pato et al . (), who found that, in addition to adults, deer could also support a high proportion of immature stages. The median number of ticks infesting roe deer was similar in both areas (Table ) and the differences were not significant using the Kruskal–Wallis test ( P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not have data on infection prevalence for the largest mammals in our analysis: Red deer (Cervus elaphus) and Roe deer. Studies that were not incorporated in our selection, for reasons outlined above, show that Roe deer have high levels of antibody in their blood, and low infection prevalence in tissues [150][151][152] . These findings support the hypothesis that B. burgdorferi is unable to circumvent the host complement of deer 131,153 , which could also explain the incapability of deer to transmit Borrelia spirochaetes 48 .…”
Section: Infection Prevalence Of Host Species With B Burgdorferimentioning
confidence: 99%